On the universality of conditions in large scale residential architecture - Vassiliev, Nikolai (project baikal, 2026)
The article examines the applicability of the most widespread modernist structural principle of a frame residential building in connection with folk and vernacular architecture in the conditions of dry subtropics. The desire to radically reduce the construction cost and examples from automobile and ship construction inspired architects of the first half to the middle of the 20th century to develop a type of house with a load-bearing steel or reinforced concrete frame and a flat roof, which paradoxically reminded of local types of non-professional architecture dating back thousands of years.
Keywords: early modernism; vernacular architecture; housing; mass construction